The proposed new integrated of performance measurements (M score) for Islamic banks - Memiyanty, Abdul Rahim; Abdul Rahman, Abdul Rahim; Syed Jaafar Alhabshi, Syed Musa (American Scientific Publishers, 2016)
The aim of this study is to conceptually analyze and develop Islamic economic performance measurement indicators (M Score) for Islamic banks. In developing the indicators, the study has developed and adapted the performance measurement indicators based on the well-established Islamic economic objectives by selected scholars. The main argument of this study is that Islamic banks’ performance should be measured using unique and specific objective indicators that will reflect their Islamic economic objectives. Hence, it is of vital importance to translate the normative Islamic economic objectives that require broader and more societal approach of measurement rather than focusing on the narrow financial measurement of conventional finance. This study is conducted to validate and test the level of acceptability of M Score for Islamic banks. The M Score is very useful to be tested for future empirical studies.